The American Society of Pediatric Hematology/Oncology workforce assessment: Part 2—Implications for fellowship training. Issue 2 (25th October 2017) - Leavey, P. J.; Hilden, J. M.; Matthews, D.; Dandoy, C.; Badawy, S. M.; Shah, M.; Wayne, A. S.; Hord, J.; ,
Abstract: The American Society of Pediatric Hematology/Oncology (ASPHO) solicited information from division directors and fellowship training program directors to capture pediatric hematology/oncology (PHO) specific workforce data of 6 years (2010–2015), in response to an increase in graduating fellows during that time. Observations included a stable number of physicians and advanced practice providers (APPs) in clinical PHO, an increased proportion of APPs hired compared to physicians, and an increase in training‐level first career positions. Rapid changes in the models of PHO care have significant implications to current and future trainees and require continued analysis to understand the evolving discipline of PHO.